The Role of Cycling on Hypertense People - Kusnanda Nurrafi’u, Gizalias; Zufar Hafizh Effendi, Muhammad; Laksmita Pramesty, Chandra; Brita Maharani, Salsabilla; Castyana, Billy (Sports Medicine Curiosity Journal, 2023)
Cycling is an activity that people do every day, but in its development, cycling is not always done by most people. Cycling is carried out as a support for daily activities that have benefits for the health of the body such as reducing excessive blood pressure levels or can be referred to as preventing hypertension. Hypertension generally occurs in the elderly, but several studies have shown that hypertension also occurs in adolescence and is realized during the last decade. Through this literature review method by collecting several scientific articles or reference books as an understanding of a problem. From here, it is organized into four stages, namely: first, looking for scientific articles or reference books. Second, evaluate the literature review sources. Third, identify themes and theoretical gaps with existing conditions in the field. Fourth, namely the presentation and conclusion of the article review process. After doing this method, the author concludes that cycling has a pretty good role for people with hypertension, one of which is when after doing cycling, the body's health condition is controlled and makes excessive stress disappear, so cycling is recommended for people with hypertension.